Characterization of Soils in Teak Forests, Grassland and Agricultural Lands of Basaltic Origin in Central India - Wankhede, S. R.; Prasad, Jagdish (Indian Forester, 2008)
Three soils, each in Nagpur, Seoni and Mandla districts of Central India supporting teak forest, grassland and crops, in toposequence were characterised for morphological, physical and chemical properties and in particular organic carbon. In general, soils were darker barring few exceptions. The soils are clayey dominated by smectitic mineralogy. The pH of forest soils was relatively lower than grassland and cultivated ones. The organic matter carbon content and stocks were higher in forest soils than the soils of grassland and cultivated.